EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) SEBAGAI INHIBITOR PERTUMBUHAN BAKTERI ZOONOSIS Proteus mirabilis YANG DIISOLASI DARI DAGING AYAM BROILER - Abdul Wahid Jamaluddin; Lucia Musimin; M Natsir Djide (As-Syifaa Jurnal Farmasi, 2018)
This research  exploring the potential of antibacterial compounds from herbs to be important to do considering the number of cases of bacterial resistance. Proteus itself is one of the bacteria zoonosis or bacteria that can transfer the disease from animals or products of animal origin to humans. This study aims to ascertain whether guava leaf extract has antimicrobial activity against Proteus mirabilis, zoonotic bacteria from broiler chicken sold in several traditional markets in Makassar. The method used for the identification of Proteus mirabilis with PCR. Positive samples from PCR were then continued for the antimicrobial activity test of Guava Leaf Extract (Psidium guajava L.) using concentrations of 10%, 20%, and 30% using 10% DMSO solvent. In this research, there were 3 Positive samples (B2, D4 and PT4) as Proteus mirabilis indicated by Band at 532bp. The results of the antimicrobial activity test of Guava Leaf Extract showed antimicrobial activity against ATCC 43071, B2, D4 and PT4 Proteus mirabilis where the largest Inhibition Zone was shown by Concentrations of 30%